Examining the effect of the secondary flow-field on polymer electrolyte fuel cells using X-ray computed radiography and computational modelling. (8th January 2019) - Kulkarni, Nivedita; Meyer, Quentin; Hack, Jennifer; Jervis, Rhodri; Iacoviello, Francesco; Ronaszegi, Krisztian; Adcock, Paul; Shearing, Paul R.; Brett, Daniel J.L.
Abstract: Flow-fields are key factors in determining the operation of fuel cells. While extensive work has been conducted to develop and optimise the reactant flow and current collection performance of polymer electrolyte membrane fuel cell (PEMFC) components, there is a factor that remains largely unaccounted for. Depending on how a membrane electrode assembly (MEA) is incorporated into a cell, there will often be a small gap between the edge of the gas diffusion layer (GDL) and the seal or bipolar plate. This gap acts as a 'secondary flow-field' (SFF) that can bypass or affect/augment the conventional or 'primary flow-field'. Understanding how this affects performance (either positively or adversely) is essential for holistic flow-field design. This paper describes the issues associated with the SFF, examines how cell compression affects its width due to lateral expansion of the GDL and discusses the results of a 3-D computational model that investigates the effect of the SFF during dead-ended anode (DEA) operation for a fuel cell without a macroscopic (conventional) anode flow-field. Highlights: The gap around GDL and seal represents a secondary flow-field. Effect of GDL compression on its lateral expansion quantified. Secondary flow-field improves dead-ended operation.